Fault Diagnosis Research on Impact System of Hydraulic Rock Drill Based on Internal Mechanism Testing Method - Yelin Li; Youxin Luo; Xiao Wu (Shock and Vibration)
In the production and manufacturing process of hydraulic rock drill, there are small impact energy and low impact frequency, and a fault diagnosis method based on the internal mechanism testing and testing of the hydraulic rock drill is proposed. This method is used to test the change law of hydraulic oil in the rock drill, by retaining the test holes on the cylinder body and other important components of the hydraulic rock drill. At the same time, the mathematical method is used to deal with the test curve, and the influence of pressure pulsation characteristics of the front and rear chambers of the impact piston and the left and right valve chambers of the reversing valve on the impact performance of the rock drill is analyzed. Based on Newton’s law, the model of the impact piston and reversing valve is established. According to the velocity and other parameters of the impact piston, the size of the impact piston switch point is calculated. The coupling between the movement of the impact piston and the movement of the reversing valve is analyzed according to the model established. Comparing the results of the experimental data, the correctness of the fault diagnosis analysis method and model is verified. The effect of the fault rock drill and the improved model is compared, and the theoretical basis is provided for the fault diagnosis of the rock drill and the design of a new type of rock drill.